2020
DOI: 10.1177/1971400920970918
|View full text |Cite
|
Sign up to set email alerts
|

Signal intensity pattern of the normal oculomotor nerve on contrast-enhanced 3D FLAIR at 3.0 T MRI

Abstract: Purpose The aim of this study was to depict the signal intensity pattern of the normal oculomotor nerve demonstrated on contrast-enhanced three-dimensional fluid-attenuated inversion recovery images. Materials and methods Eighty-one patients were included in the study. Contrast-enhanced three-dimensional fluid-attenuated inversion recovery images with magnetisation-prepared rapid acquisition were reconstructed and evaluated in the coronal plane. The signal intensity of the cisternal segment of the oculomotor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
1
0
3
Order By: Relevance
“…21 Accumulating studies have confirmed that 3.0T MRI, especially the 3D-FLAIR sequence, has good sensitivity and specificity to the alterations in ISSNHL inner ear signals. 17,22 The application of 3D-FLAIR MRI can assist clinicians to find different pathological changes in the inner ear on time. Therefore, 3D-FLAIR MRI has a potentially important clinical value for the possible pathological mechanism and prognosis assessment of ISSNHL.…”
Section: ■ Discussionmentioning
confidence: 99%
“…21 Accumulating studies have confirmed that 3.0T MRI, especially the 3D-FLAIR sequence, has good sensitivity and specificity to the alterations in ISSNHL inner ear signals. 17,22 The application of 3D-FLAIR MRI can assist clinicians to find different pathological changes in the inner ear on time. Therefore, 3D-FLAIR MRI has a potentially important clinical value for the possible pathological mechanism and prognosis assessment of ISSNHL.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Signalverstärkungen im zisternalen Segment sind bei sog. ischämischen, mikrovaskulären Paresen schon mehrfach beschrieben worden 16 , 17 . Bezeichnenderweise fehlt bei manchen Signalverstärkungen – so wie in unserem genannten Fallbeispiel – das klinische Korrelat einer Hirnnervenparese 16 , 17 .…”
Section: Pathologien Im Zisternalen Segment Des III Iv Und Vi Hirnnervenunclassified
“…ischämischen, mikrovaskulären Paresen schon mehrfach beschrieben worden 16 , 17 . Bezeichnenderweise fehlt bei manchen Signalverstärkungen – so wie in unserem genannten Fallbeispiel – das klinische Korrelat einer Hirnnervenparese 16 , 17 . Obwohl klinisch nur eine einseitige Okulomotoriusparese vorliegt, zeigt der linke nicht betroffene N. oculomotorius eine nahezu identische Signalverstärkung.…”
Section: Pathologien Im Zisternalen Segment Des III Iv Und Vi Hirnnervenunclassified
See 1 more Smart Citation